Improving Mathematics Learning Outcomes through Model Application Cooperative Learning Type Student Teams Achievement Division (STAD) - Fattah, Abdul (MACCA : Science-Edu Journal, 2024)
This research is classroom action research which was carried out in two cycles and aims to find out whether the Mathematics learning outcomes of Class VI MIN 2 Bulukumba students who are taught using the STAD type cooperative learning model can improve. The subjects of this research were 20 students of class VI MIN 2 Bulukumba, even semester of the 2022/2023 academic year. The research results have a positive impact on student learning outcomes. Learning outcomes in cycle I had the lowest score of 41, the highest score of 78 and the average score of 65.95. Meanwhile in cycle II the lowest score was 69, the highest score was 100 and the average score was 83.55. The percentage of learning completeness in cycle I was 40% and the percentage of learning completeness in cycle II was 95%, this shows an increase of 55%.